2021
DOI: 10.1111/cbdd.13948
|View full text |Cite
|
Sign up to set email alerts
|

Glucosyl‐1,2,3‐triazoles derived from eugenol and analogues: Synthesis, anti‐Candida activity, and molecular modeling studies in CYP‐51

Abstract: This work describes the synthesis, anti-Candida, and molecular modeling studies of eighteen new glucosyl-1,2,3-triazoles derived from eugenol and correlated phenols. The new compounds were characterized by combined Fourier

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Furthermore, in order to verify other possible mechanisms of action of chlorogenic acid, it was found that it exhibited promising affinity energy in the complex with CYP51, an enzyme involved in ergosterol synthesis and, therefore, essential for membrane stability and survival of the fungus [81], and with Yeast Cytochrome BC1 Complex. In a study carried out by [82] it was verified that the inhibition of cytochrome BC1 is related to the reduction of resistance to azoles, the impediment of the fungus' adaptation to nutrient deprivation, the sensitization of C. albicans to macrophage attack and reduced virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in order to verify other possible mechanisms of action of chlorogenic acid, it was found that it exhibited promising affinity energy in the complex with CYP51, an enzyme involved in ergosterol synthesis and, therefore, essential for membrane stability and survival of the fungus [81], and with Yeast Cytochrome BC1 Complex. In a study carried out by [82] it was verified that the inhibition of cytochrome BC1 is related to the reduction of resistance to azoles, the impediment of the fungus' adaptation to nutrient deprivation, the sensitization of C. albicans to macrophage attack and reduced virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Some glucosyl‐1,2,3‐triazoles derived from eugenol and substituted phenols were synthesized by Magalhães et al. (2021). The peracetylated triazole hybrids I1 (a eugenol derivative) and I2 (a dihydroeugenol derivative) indicated the most promising antifungal activity against Candida krusei , with the IC 50 values of 26.1 and 25.98 μM, respectively.…”
Section: Antifungal 123‐triazole Hybridsmentioning
confidence: 99%
“…Acetyl groups play a key role in the antifungal activity of peracetylated compounds ( I1 ‐ I2 ) and probably might act as prodrugs, compared with their deacetylated forms. Molecular docking and molecular dynamics studies have revealed that the antifungal activity of some peracetylated triazole compounds might be due to the inhibition of 14α‐lanosterol demethylase and disruption of the fungal membrane (Magalhães et al., 2021).…”
Section: Antifungal 123‐triazole Hybridsmentioning
confidence: 99%
“…It displayed a wider range of biological activities than compound 39. Overall, the molecular modelling studies revealed that compounds 17 antifungal activity is attributed to the inhibition of CYP51, which prevents the formation of fungal ergosterol [110]. Pharmaceutics 2023, 15, x FOR PEER REVIEW 12 of 23…”
Section: Eugenolmentioning
confidence: 99%